2016
DOI: 10.1002/smll.201502458
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Corona of Plant Virus Nanoparticles Influences their Dispersion Properties, Cellular Interactions, and In Vivo Fates

Abstract: Biomolecules in bodily fluids such as plasma can adsorb to the surface of nanoparticles and influence their biological properties. This phenomenon, known as the protein corona, is well established in the field of synthetic nanotechnology but has not been described in the context of plant virus nanoparticles (VNPs). We investigated the interaction between VNPs derived from Tobacco mosaic virus (TMV) and plasma proteins, and found that the VNP protein corona was significantly less abundant compared to the corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 59 publications
3
71
0
Order By: Relevance
“…Triplicates of sulfo-Cyanine5 azide (Cy5)-labeled TMV-RGD (300 nm long) were added at a concentration of 100,000 particles/cell and incubated for 3, 1.5, and 0.5 h at 37 °C, 5% CO 2 . The Cy5-TMV-RGD particles were synthesized and characterized as described by Pitek et al 27 Control experiments were conducted, in triplicate, with no particles present. Post incubation with TMV nanoparticles, cells were spun down at 500 g for 4 min.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Triplicates of sulfo-Cyanine5 azide (Cy5)-labeled TMV-RGD (300 nm long) were added at a concentration of 100,000 particles/cell and incubated for 3, 1.5, and 0.5 h at 37 °C, 5% CO 2 . The Cy5-TMV-RGD particles were synthesized and characterized as described by Pitek et al 27 Control experiments were conducted, in triplicate, with no particles present. Post incubation with TMV nanoparticles, cells were spun down at 500 g for 4 min.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Antibodies against TMV, therefore, may be prevalent in the human population. Indeed, we have previously found binding of immunoglobulins to TMV upon incubation in human plasma collected from random donors [45]. If antibodies are not already present, these are developed after repeat administration of TMV-based therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, SA coatings outperformed PEG coatings in terms of antibody evasion and pharmacokinetics, resulting in effective evasion from antibody recognition and 10-times increased circulation half-life of t 1/2 ~ 100 mins vs. the PEGylated TMV formulation. Macrophage uptake was reduced compared to ‘naked’ TMV but no differences were observed comparing SA- vs. PEG-coated TMV, indicating that antibody-mediated clearance is the dominating factor for the rapid plasma clearance of TMV (we have previously shown that the protein corona formed on ‘naked’ TMV in plasma consists of immunoglobulins [45]). To be effective for systemic and repeat administration, evasion of antibody surveillance is an important goal.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies will provide insight into the clearance and biodistribution of the particles, as well as the behavior of the particles in the presence of serum proteins, which will be important considerations for future translation. 31 …”
Section: Resultsmentioning
confidence: 99%